The Influence of Population Policy Implementation and Service Quality on Community Satisfaction in Making Electronic ID Cards at the Badung Civil Registry Office - Rakhman, Saifur (International Journal of Entrepreneurship and Business Management, 2023)
This research aims to determine the impact of population policy implementation and service quality on community satisfaction in making electronic ID cards. This research uses quantitative research methods with a causality research design. The sample taken was 100 respondents with the sampling technique in this research being accidental sampling. The analysis technique for this research uses descriptive analysis. The results of the research show that the implementation of population policy has an influence on the satisfaction of applicants for making Electronic KTPs at the Population and Civil Registration Service of Badung Regency, the quality of service has an influence on the satisfaction of applicants for making Electronic KTPs at the Population and Civil Registration Service of Badung Regency and the implementation of population policy and service quality has an effect of 64 .1%, to the satisfaction of applicants for making Electronic KTPs at the Badung Regency Population and Civil Registration Service. This can be an input for the leaders and employees of the Badung Civil Registry Office to continue to innovate in providing better services by providing more detailed attention and explanations to applicants who they feel do not understand.